Production of yacon plantlet (Polymnia sonchifolia poep. et endl.) in different organic fertilization - da Silva, MAS; Hidalgo, A. D.; de Morais, LAS; Goncalves, M. D.; da Silva, SMP (International Society Horticultural Science, 2002)
The work was carried out in nursery of the Agronomical Science College (ASC) UNESP-Botucatu, in period from September 21(st) to October 31(st) 2000. The propagation material (rhizophores) was obtained from plants, which were cultivated in the area of ASC. The rhizophores were selected according to their vigor and size. Healthy rhizophores were chosen between 15 and 25 g, which were treated with benomil (0,6%, 10 minutes). As a basic commercial substratum Solomix((R)) was used with mixing cattle manure and chicken manure in the following proportions: T1- pure substratum; T2 - substratum + cattle manure (1:1), T3- substratum + cattle manure (2:1); T4- substratum + chicken manure (4:1). The yacon rhizophores presented good shoots in all substrata with exception of T4. For all parameters no significant difference between the pure commercial substratum and its mixture with cattle manure were observed; however, the addition the chicken manure in the studied proportions revealed harmful effect on the survival and development of the plantlets. The results indicated, that the viability of smaller size rhizophores was higher as the size conventionally used in Brazil (60 to 80 g).
Keywords: tuberous root; substratum; organic production